FACTORS INFLUENCING THE FORMATION OF SPEECH CULTURE (International journal of artificial intelligence, 2026)
This article examines the factors influencing the development of students' speech culture. It also discusses the significance and necessity, content and essence, and specific characteristics of the factors influencing the development of speech culture in future teachers.